Perceived Social Support and Its Effects on Changes in the Affective and Eudaimonic Well-Being of Chilean University Students - Cobo-Rendón, Rubia; López-Angulo, Yaranay; Pérez-Villalobos, María Victoria; Díaz-Mujica, Alejandro (Frontiers in Psychology, 2020)
The beginning of university life can be a stressful event for students, the close social relationships that they can experience can have positive effects on their well-being. The objective of this paper is to estimate the effect of perceived social support in the changes of the affective and eudaimonic well-being of Chilean university students during the transition from the first to the second academic year. 205 students participated (63.90% men and 36.09% women) with an average age of 19.14 (SD = 1.73), evaluated during their first academic year (2017) and the succeeding one (2018). For the evaluation of perceived social support, the Spanish version of the Perceived Social Support Questionnaire “MSPSS” was used and PERMA-profiler was used to measure affective and eudaimonic well-being. Changes through the time of affective well-being and social support and the correlations between the variables were analyzed. Changes in the perception of social support were analyzed according to four categories of well-being. Results indicated that the perception of students' social support did not change over time. Statistically significant differences were found in affective well-being scores in the two measurements, being significantly higher in the first measurement than in the second one. More than 50% of the participants presented high well-being. The perception of social support is associated with the two types of well-being. Students who had a high affective and eudaimonic well-being had a greater perception of general social support than the groups of positive evolution and the low well-being. In the case of the friends and family support dimensions, the perception in the high well-being group concerning the low-scale group is greater. The perception of support that students had during the beginning of their university life benefits their general well- being, which contributes to their mental health